Ketahanan Pangan Sebagai Instrumen Pertahanan: Integrasi Food Estate Ke Dalam Logistik Militer - Kiki Lestari; Agung Prapsetyo; Frangky Silitonga (JURNAL TEKNIK SIPIL PERTAHANAN, 2026)
Disruption of the global food supply chain due to climate change, conflicts between countries based on interests, and pandemics have exposed systemic vulnerabilities for Indonesia, including the risk of food weaponization and military logistics paralysis when foreign supplies are cut off (FAO et al., 2023; D'Odorico et al., 2018). Traditionally, food security has been understood as a welfare issue, not a strategic defense component. This study aims to reconceptualize food security as a defense instrument through integrating the Food Estate program into the Indonesian National Military (TNI) logistics system. Using a qualitative case study approach on Central Kalimantan and Merauke Food Estates for the 2021–2026 period, this research finds: (1) food estate production capacity is mathematically sufficient to meet all TNI food logistics needs, with rice fulfillment potential reaching 520%; (2) no formal mechanism connects food estate production with military logistics consumption; (3) food self-sufficiency serves as a force multiplier in crises because TNI does not compete with civilians; (4) integration requires defense doctrine revision and a cross-ministerial coordinating body. This study recommends that Food Estates be designed as a Strategic Defense Logistics Zone with a long-term off-take agreement between the Ministry of Defense and the Ministry of Agriculture, along with a minimum 90-day logistics reserve for units in conflict-prone border areas.